(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Changes in the forest sector in recent years have been caused by different reactions of the domestic and foreign markets at different levels. The resources of every country are the subject of disputes and sometimes wars. It was found that on the path of every business, especially the one related to resources, the question of assessing its competitiveness arises. Peculiarities of the state and changes in the activities of individual branches (forestry enterprises) of the Western Interregional Forestry and Hunting Administration (WIFHA) were revealed. Indicators that are key to identifying competitive individual branches (forest farms) of WIFHA were evaluated and analyzed. Directions for managing the competitiveness of individual WIFHA branches are proposed, taking into account changes and peculiarities of product sales. Information analysis approaches were combined to get the whole picture of the companies. At the first stage, calculations were carried out regarding the effectiveness of individual forestry operations, which were previously an entity of the Lviv Regional Forestry and Hunting Management, which is now, along with two other administrations (Ivano-Frankivsk and Zakarpattia), an integral part of the WIFHA. At the second stage, competitiveness analysis was conducted. Based on competitive profile matrix ranking was made to outline the enterprises with the best business solutions in the conditions of uncertainty. At the third stage, some recommendations were provided to Quantitative and qualitative analysis of the activity and development of the some affiliates of WIFHA was conducted. General conclusions were made, such as: pay attention to seed centers and non-wood products; improvement of product sales; expanding the use of plots for recreational purposes and increasing advertising of recreational services; improvement of management approaches at the state level for interregional, as well as individual offices / branches; introduction of modern models; further work on Internet presence and presentation of activity results through networking and social media (YouTube, Instagram, Facebook, etc.); presentation of information also in English.